2012
DOI: 10.1093/ejcts/ezs199
|View full text |Cite
|
Sign up to set email alerts
|

Selective pulmonary pulsatile perfusion with oxygenated blood during cardiopulmonary bypass attenuates lung tissue inflammation but does not affect circulating cytokine levels

Abstract: sPPP attenuates alveolar inflammation, as demonstrated by the lower neutrophilic/lymphocytic alveolar infiltration, and the secretion of anti-inflammatory rather than proinflammatory mediators.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 23 publications
2
19
0
Order By: Relevance
“…Thus, we used hypothermic LPD solution for pulmonary artery perfusion in this study to reduce those CPB-related adverse effects on lung. Numerous studies have demonstrated that hypothermic pulmonary perfusion can effectively reduce pulmonary metabolic rate, decrease OFR production, and increase plasma colloid osmotic pressure to prevent pulmonary edema [14], [18], [19]. Our results show that pulmonary artery perfusion with TNF-α Ab in hypothermic LPD significantly reduces CPB-induced apoptosis and prevents pulmonary edema.…”
Section: Discussionsupporting
confidence: 55%
“…Thus, we used hypothermic LPD solution for pulmonary artery perfusion in this study to reduce those CPB-related adverse effects on lung. Numerous studies have demonstrated that hypothermic pulmonary perfusion can effectively reduce pulmonary metabolic rate, decrease OFR production, and increase plasma colloid osmotic pressure to prevent pulmonary edema [14], [18], [19]. Our results show that pulmonary artery perfusion with TNF-α Ab in hypothermic LPD significantly reduces CPB-induced apoptosis and prevents pulmonary edema.…”
Section: Discussionsupporting
confidence: 55%
“…As reported in animal studies, [13][14][15][16] small randomised trials and observational studies in infants 18 19 and adults, [22][23][24][25] we have now evaluated and confirmed in a clinical setting with adult patients with COPD, that pulmonary artery perfusion with oxygenated blood during CPB results in a higher postoperative oxygenation. This was obtained without an increased incidence of complications or significant prolongation of the surgical procedure.…”
Section: Discussionmentioning
confidence: 53%
“…It has now been confirmed in several animal models that bronchial artery blood flow is decreased substantially during CPB, and although exposure to CPB alone is enough to cause pulmonary injury, concomitant cessation of pulmonary artery flow contributes significantly to the development of postoperative pulmonary dysfunction. [9][10][11][12] The results of animals studies, [13][14][15][16] small randomised trials in infants with congenital heart disease 17-20 and inconclusive minor randomised trials and observational studies in adults [21][22][23][24][25] indicates that pulmonary artery perfusion with normothermic oxygenated blood preserves postoperative oxygenation. Further, lung transplantation experiences has shown that pulmonary artery perfusion with a hypothermic preservation solution protects the lungs from warm ischaemic injury during storage and transplantation.…”
Section: Introductionmentioning
confidence: 99%
“…Clinical studies in settings resembling our study are less sanguine. Selective continuous pulmonary artery perfusion flows of 7 ml/kg/min, comparable to those used in our study, in low-risk adult patients during on-bypass coronary revascularization resulted in no significant clinical benefits (14, 15) despite slightly improved pulmonary perfusion indices and decreased pulmonary tissue inflammatory cytokine production. Importantly, Kiessling et al (5) reported an absence of clinical benefits despite small trends toward decreased pulmonary tissue-generated inflammatory markers in a study of intermittent selective pulmonary perfusion in high-risk pulmonary patients undergoing on-bypass coronary revascularization.…”
Section: Discussionmentioning
confidence: 57%
“…Even such well-established concepts as the deleterious effects of inflammatory cytokines still await their correlation with specific clinical end-points. While Siepe et al (20) attributed the protective effects of pulmonary perfusion during CPB to the decreased pulmonary tissue expression and blood concentration of inflammatory cytokines, such as IL-6, IL-8, IL-10, and TNF-α, and others (5, 15, 19) could not reproduce these effects. Likewise, despite avoidance of CPB, pulmonary atelectasis and activation of inflammatory cascades associated with pulmonary ischemia–reperfusion injury, off-bypass technique of coronary revascularization offers only a modest clinical impact on pulmonary outcomes in patients with severe pulmonary disease (2123).…”
Section: Discussionmentioning
confidence: 99%